Neurological and Mental Disorders 2020
DOI: 10.5772/intechopen.89477
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts from Height and Injury Patterns: An Analysis of 64 Cases

Abstract: Falls from height are a common cause of death and disability. A majority of free falls occur accidentally and only a minority result from suicidal behaviour. Adolescents in many countries show high rates of suicide attempts and their repetition is a common feature. We describe the demographic characteristics of these patients, their psychiatric diagnosis at the time of the attempt and the injury patterns. We present 64 patients who sustained injuries as a result of a fall from height. They were divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…While the article by Yoo et al 1) states that most suicide attempt survivors primarily had a prior diagnosis of depression, other studies have noted that schizophrenia could be the predominant illness. 4 5 6) In another study, prior diagnosis of a personality disorder was shown to be more notable than depression in intentional fallers. 7) Therefore, it cannot be concluded that a specific mental illness will predict that one will seek to intentionally fall.…”
mentioning
confidence: 95%
“…While the article by Yoo et al 1) states that most suicide attempt survivors primarily had a prior diagnosis of depression, other studies have noted that schizophrenia could be the predominant illness. 4 5 6) In another study, prior diagnosis of a personality disorder was shown to be more notable than depression in intentional fallers. 7) Therefore, it cannot be concluded that a specific mental illness will predict that one will seek to intentionally fall.…”
mentioning
confidence: 95%